A Blockchain-Based Hierarchical Authentication Scheme for Multiserver Architecture. (23rd April 2021) - Wu, Miqi; You, Lin; Hu, Gengran; Li, Liang; Cao, Chengtang
Abstract : In a multiserver architecture, authentication schemes play an important role in the secure communication of the system. In many multiserver authentication schemes, the security of the mutual authentications among the participants is based on the security of the registration center's private key. This centralized architecture can create security risks due to the leakage of the registration center's private key. Blockchain technology, with its decentralized, tamper-proof, and distributed features, can provide a new solution for multiserver authentication schemes. In a lot of multiserver authentication schemes, users' permission is generally controlled by the registration center (RC), but these permission control methods cannot be applied in the decentralized blockchain system. In this paper, a blockchain-based authentication scheme for multiserver architecture is proposed. Our scheme provides a hierarchical authentication method to solve the problems of user permission control and user revocation caused by no registration center. The security of our scheme is formally proved under the random oracle model. According to our analysis, our scheme is resistant to attacks such as impersonation attacks and man-in-the-middle attacks. In addition, our performance analysis shows that the proposed scheme has less computation overhead.